2023
DOI: 10.1002/adma.202309130
|View full text |Cite
|
Sign up to set email alerts
|

Smart‐Responsive HOF Heterostructures with Multiple Spatial‐Resolved Emission Modes toward Photonic Security Platform

Yuanchao Lv,
Jiashuai Liang,
Zhile Xiong
et al.

Abstract: Luminescent hydrogen‐bonded organic frameworks (HOFs) with the unique dynamics and versatile functional sites hold great potential application in information security, yet most of responsive HOFs focus on the single‐component framework with restrained emission control, limiting further applications in advanced confidential information protection. Herein, we report the first smart‐responsive HOF heterostructure with multiple spatial‐resolved emission modes for covert photonic security platform. The HOF heterost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Then BA-N can be easily obtained by a trimerization reaction of TFMABr in water. The structure of BA-N was confirmed by 1 H NMR, 13 C NMR and 19 F NMR in deuterated DMSO (Figure S1-S3). Possible mechanism of the trimerization reaction of TFMABr has been proposed and shown in Scheme S1.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Then BA-N can be easily obtained by a trimerization reaction of TFMABr in water. The structure of BA-N was confirmed by 1 H NMR, 13 C NMR and 19 F NMR in deuterated DMSO (Figure S1-S3). Possible mechanism of the trimerization reaction of TFMABr has been proposed and shown in Scheme S1.…”
Section: Resultsmentioning
confidence: 86%
“…[12] Zhang et al reported the first intelligent HOF heterostructure with multiple spatially resolved emission modes for covert photonic security platforms. [13] Chi et al developed a flexible HOF that can dynamically adjust pore size to accommodate guest molecules of different sizes in response to external stimuli. [14] However, the current response of HOFs to external environmental stimuli is limited to the phase transitions such as the opening and closing of their pores.…”
Section: Introductionmentioning
confidence: 99%
“…HOFs are more versatile due to their soft and adjustable pores, and together with other applications, have been utilized for the development of luminescent hosts. [160][161][162][163][164] H. Wang et al utilized the tetrahedrally functionalized AIE skeleton of TPE-tetra(amidinium) ions TPE 4+ for the development of periodic porous and fluorescent HOFs with a range of dicarboxylic acids including 2TP, 2BPY, 2BPH and 2TPh. Interestingly, the resultant HOFs were blue emitting with finely tuned emission wavelengths ranging between 453-487 nm and quantum yields of 4.6-3.6%.…”
Section: Multi-component Crystalsmentioning
confidence: 99%